2004
DOI: 10.1021/jm049903j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Inactivation of β-Lactamases by Novel 6-Methylidene Penems Elucidated Using Electrospray Ionization Mass Spectrometry

Abstract: The reactions of 6-methylidene penems 4-7 with beta-lactamases (TEM-1, SHV-1, Amp-C) were characterized by electrospray ionization mass spectrometry (ESI-MS). The kinetics of the reactions were monitored, demonstrating that only one penem molecule reacts to form an acyl-enzyme complex. For penem 5, the ESI-MS/MS spectrum of the hydrolysis product produced in the reaction was identical to the spectrum generated from a synthesized dihydro[1,4]thiazepine 10, confirming the rearrangement of the penem ring system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Other classes of β-lactamase inhibitors undergo chemical rearrangements from their initial acyl-enzyme species, and such rearrangements are observable at high ratios of inhibitor to enzyme (17,18). To investigate this possibility, a high concentration of avibactam was incubated with TEM-1, and the off-rate was measured (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other classes of β-lactamase inhibitors undergo chemical rearrangements from their initial acyl-enzyme species, and such rearrangements are observable at high ratios of inhibitor to enzyme (17,18). To investigate this possibility, a high concentration of avibactam was incubated with TEM-1, and the off-rate was measured (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, mass spectrometry studies demonstrated that the methylidene penem inhibition pathway does not involve fragmentation in the active site (119,250,406). When TEM-1, P99, and the class A ␤-lactamase from B. cereus I were inactivated by BRL 42715, spectra showed a mass increases equivalent to the molecular masses of the inhibitor plus the enzyme (119).…”
Section: Penemsmentioning
confidence: 99%
“…Thus, we wondered if penem inhibitors that possess an sp 2 -hybridized C 3 carboxylate (a property resembling a characteristic of carbapenems), a complex and reactive R1 side chain, and inactivation chemistry different from that of clavulanic acid could be exploited to inhibit KPC enzymes (41). The methylidene inhibitors penem 1 and penem 2 have dihydropyrazolo [1,5-c] [1,3]thiazole and dihydropyrazolo [5,1-c] [1,4] thiazine moieties, respectively (see Fig.…”
mentioning
confidence: 99%